Euro Area Enlargement: Dilemmas and Prospects - Dulkys, Arūnas (Ekonomika, 2008)
Almost all member states of the new European Union declared their wish to introduce the euro in the near future. The decision of the European Union institutions concerning Lithuania revealed the peculiarities and problems of the euro area enlargement to the Central and Eastern European countries, which are not easy to explain on a purely economic basis while all of them share the same market, and the economic growth restrictions imposed on them are quite disadvantageous. The article discusses a hypothesis that decision on the expansion of the euro zone is determined not only by fulfilment of the Maastricht criteria, but also by a complex of macroeconomic, institutional and political reasons. This article aims to discuss the problem related to the monetary integration in the Central and Eastern Europe. Of no less importance is the progress in implementing measures provided in the governments’ programmes, convergence programmes and national plans of the euro adoption of the countries. Conclusions and proposals are presented on how the Central and Eastern European states must strengthen the monitoring of the monetary integration under different standpoints and interests of the players in the decision-making process regarding the euro area membership.